THE IMPACT OF MIGRATION PROCESSES ON THE SOCIO-ECONOMIC DEVELOPMENT OF THE STATE (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the impact of migration processes on the socio-economic development of the state in conditions of military transformations and demographic instability. The theoretical basis of the study is formed on the basis of a generalization of domestic scientific approaches to the interpretation of migration as a multidimensional phenomenon that combines demographic, economic and security characteristics. The content of the categories of migration analysis is disclosed, in particular, the migration balance, population reproduction, demographic security and labor mobility. It is substantiated that external forced migration after 2022 has become a factor in structural changes in the age configuration of the population, the regional distribution of labor potential and financial flows of the state. The empirical part is based on a generalization of current statistical data from international and national institutions on the scale of Ukrainian citizens' stay abroad, the age and regional structure of refugees, as well as the dynamics of net migration outflow. It is established that the dominance of a young and able-bodied contingent among those who left creates long-term restrictions on the labor market, innovative development, and budget sustainability. The impact of migration processes on the gross domestic product, tax base, social security system, and territorial development is analyzed. A systematization of the consequences of external migration by spheres of influence is proposed, taking into account short-term and medium-term effects and macroeconomic risks. The conclusion is made about the need to integrate the migration factor into the strategic planning of post-war recovery, the formation of reintegration tools and stimulating the return of citizens, as well as strengthening the policy of restoring human capital as a basic resource for the socio-economic stability of the state.